Proteins Specified by Herpes Simplex Virus VI. Viral Proteins in the Plasma Membrane - Heine, Jochen W. (1972)
Previous papers in the series have shown that the surface membranes of herpesvirus-infected cells acquire new immunological specificities and that purified infected cell membrane preparations, characterized by their physical properties rather than topology in the cell, contain new glycoproteins genetically determined by the virus. In this study, we prepared purified plasma membrane identified by its 5′ nucleotidase, fucose, and reduced nicotinamide adenine dinucleotide-diaphorase content. Analysis of the membrane proteins and glycoproteins by electrophoresis in acrylamide gels indicated the following. (i) Purified plasma membranes from infected cells contained two sets of proteins, i.e., host proteins were present both before and after infection and viral proteins were present only after infection. (ii) After infection, no appreciable selective or nonselective loss of host proteins from membranes was demonstrable. However, no new host proteins were made. (iii) Electropherograms of plasma membrane proteins from infected cells indicated the presence of at least 12 virus-specific proteins ranging in molecular weight from 25 × 10(3) to 126 × 10(3) daltons. Of these, at least nine were glycosylated. Proteins and glycoproteins with similar electrophoretic mobilities but in somewhat different ratios were also present in preparations of highly purified virions.